Analysis of The Thermodynamics Problem-solving Process Based on Polya’s Stages in High School Students - Lutfiani, Silvia; Liliawati, Winny; Samsudin, Achmad; Aviyanti, Lina (Jurnal Pendidikan Matematika dan Sains, 2026)
This research was motivated by the importance of problem-solving skills as part of the higher-order thinking skills required in physics learning, especially in complex and abstract thermodynamics materials. The complexity of materials, including internal energy, ideal gases, and the laws of thermodynamics, often caused difficulties for students in understanding and solving problems. This study aimed to analyze students’ problem-solving skills in thermodynamics based on Polya’s problem-solving stages. The research employed a survey method involving 36 students who completed a problem-solving test covering topics of internal energy, ideal gas, and the laws of thermodynamics. The overall problem-solving score was 53,59%, categorized as low. The highest achievement was in understanding the problem (64,8%, moderate), followed by devising a plan (54,01%, low), carrying out the plan (46,60%, low), and looking back (45,37%, low). These results indicated that students experienced difficulties in selecting appropriate concepts, applying relevant formulas, and evaluating solutions systematically. The findings suggested that students’ problem-solving skills in thermodynamics remained weak and required more effective instructional approaches. This study contributed to the achievement of Sustainable Development Goal 4 (Quality Education) by highlighting the need to enhance problem-solving skills to improve the quality of physics education.